2015
DOI: 10.3389/fimmu.2015.00312
|View full text |Cite
|
Sign up to set email alerts
|

CD1d Expression and Invariant NKT Cell Responses in Herpesvirus Infections

Abstract: Invariant natural killer T (iNKT) cells are a highly conserved subset of unconventional T lymphocytes that express a canonical, semi-invariant T cell receptor and surface markers shared with the natural killer cell lineage. iNKT cells recognize exogenous and endogenous glycolipid antigens restricted by non-polymorphic CD1d molecules, and are highly responsive to the prototypical agonist, α-galactosylceramide. Upon activation, iNKT cells rapidly coordinate signaling between innate and adaptive immune cells thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…Viruses do not possess lipid ligands for i NKT cell TCRs. However, infection with some viruses (e.g., dengue virus) leads to upregulated CD1d expression consistent with i NKT cell activation while certain others (e.g., herpesviruses and HIV) downregulate CD1d to plausibly evade detection by i NKT cells ( 30 , 31 ). Viral infection may also induce a shift in host cell lipid profiles, thus yielding more “antigenic” CD1d ligands ( 32 ).…”
mentioning
confidence: 99%
“…Viruses do not possess lipid ligands for i NKT cell TCRs. However, infection with some viruses (e.g., dengue virus) leads to upregulated CD1d expression consistent with i NKT cell activation while certain others (e.g., herpesviruses and HIV) downregulate CD1d to plausibly evade detection by i NKT cells ( 30 , 31 ). Viral infection may also induce a shift in host cell lipid profiles, thus yielding more “antigenic” CD1d ligands ( 32 ).…”
mentioning
confidence: 99%
“…It has been shown that iNKT cells contribute to antiviral responses although the relevant lipid antigens have not yet been defined [recently reviewed in Ref. ( 33 37 )].…”
Section: Cd1-restricted T Cellsmentioning
confidence: 99%
“…During the evolutionary arms race with the host immune system persisting viruses have developed multilayered defense strategies to interfere with antiviral CD1-restricted T cells ( 17 , 33 , 35 , 36 , 227 ). They target the CD1 antigen presentation machinery either on the transcriptional, posttranscriptional, or posttranslational level.…”
Section: Viral Evasion Of Cd1-restricted T Cellsmentioning
confidence: 99%
“…CD1d has been declared as a regulator in immune disorders such as infection, autoimmune and inflammatory diseases. By targeting NKT cells, CD1d has been revealed to function as a suppressor in tumors (1115). Although CD1d can be expressed by cells of both myeloid (monocytes and macrophages) and lymphoid lineages (16,17), as well as non-hematopoietic cells (e.g., epithelial and vascular smooth muscle cells), it is still unclear which cells are the major source of CD1d in tumors.…”
Section: Introductionmentioning
confidence: 99%